2023
DOI: 10.1080/00343404.2022.2157809
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dependence in the non-performing loans of small Italian cooperative banks

Abstract: LM test description Statistic P-value Anselin (1988) Conditional test for spatial error autocorrelation (H 0 : spatial error autoregressive coefficient equal to zero) 9.66 0.000 Conditional test for spatial lag autocorrelation (H 0 : spatial lag autoregressive coefficient equal to zero) 20.86 0.000 Baltagi et al. (2003) Joint test (H 0 : absence of random effects and spatial autocorrelation) 2843.9 0.000 Marginal test of random effects (H 0 : absence of random effects) 50.32 0.000 Marginal test of spatial auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Respondents reported that it was hard to decline such visits even when they were busy thus disrupting their plans and also tampering with their privacy. These findings were concurred by Algeri [57] who agreed that close proximity in lending enhanced supervised lending and heightened the prospects for training and advice. Carbo-Valverde [62] agreed that closer geographical proximity is associated with decreased ex ante vetting and bank's marginal screening cost.…”
Section: Loan Repayment Status Based On Sum Of Borrower-lender Distancesupporting
confidence: 55%
See 1 more Smart Citation
“…Respondents reported that it was hard to decline such visits even when they were busy thus disrupting their plans and also tampering with their privacy. These findings were concurred by Algeri [57] who agreed that close proximity in lending enhanced supervised lending and heightened the prospects for training and advice. Carbo-Valverde [62] agreed that closer geographical proximity is associated with decreased ex ante vetting and bank's marginal screening cost.…”
Section: Loan Repayment Status Based On Sum Of Borrower-lender Distancesupporting
confidence: 55%
“…Also, Negussie [56] agreed that geographic distance increases the costs of information collection and monitoring. Algeri [57] found that distance affected relationship between the borrower and the lender.…”
Section: Loan Repayment Status Based On Borrowerlender Distancementioning
confidence: 99%
“…Empirically, the spatial dependence relationship between geographic diversification and credit supply is the subject of empirical work in both developed and developing countries. Algeri et al (2023) investigate the presence of spatial dependence in the non-performing loan (NPL) ratio of small Italian cooperative banks, over the period 2011-2017. Using spatial econometrics techniques, they demonstrate that spatial and spatio-temporal variables drive bad loans in local banks.…”
Section: The Empirical Contributionsmentioning
confidence: 99%